E-Service and Features on Banking Customer Satisfaction in the Tangerang City Area - Ardiansyah PS, Tri Endi (International Journal of Managemen Analytics (IJMA), 2024)
This research aims to determine the effect of E-Service and Features on customer satisfaction levels. The research used the probability sampling technique where calculations were by using the Bernoulli formula. partially the E-Service variable has a positive effect on Customer Satisfaction, with the result tcount is higher than ttable, namely 4.495 and 1.661. The feature has a positive effect on Customer Satisfaction, the result tcount is higher than ttable, namely 6.836 and 1.661. Simultaneously the variables E-Service, and Features have a positive effect on Customer Satisfaction with Fcount being higher than Ftable or 31.666 and 3.09. The value of the multiple regression equation Y = 19.979+ .035X1 +0,468X2, and the coefficient of determination is 60.1 percent.